Resiliencia y autoestima en un estudiante universitario con ataxia de Freidreich - Moncada Torres, Karely Xiomara; Coello Torres, Ariana Margarita (Machala, 2022)
At certain times in life, a disability may appear as a result of an accident or due to a degenerative disease, such as the case study addressed in this research, which was generated from Friedreich's ataxia. A disability that occurs without warning can mean a higher bewilderment when remembering and comparing life before the event or illness. That is why the present work has as its object of study a university student with Friedreich's ataxia; thus, this study leads to raise the following scientific problem: How does resilience and self-esteem influence a university student suffering from Friedreich's ataxia? To answer this question, we have proposed as a general objective to determine the incidence of resilience and self-esteem in a student with Friedreich's ataxia. Based on the supporting theory, it has been decided to approach the present work from a qualitative / interpretative paradigm, highlighting the arguments of the hermeneutic approach that are combined in the qualitative paradigm to achieve the interpretation of the word emitted verbally by the subject under study. Therefore, to delimit the levels of resilience and self-esteem, a qualitative methodology was implemented that gives the ease of interpreting the situations that the student manifests through the interview; in this way it is intended to potentiate the object of study. The tools that were used for the collection of information was the observation in the first instance, then the interview in charge of establishing a bank of structured questions, likewise the application of the Rosemberg scale designed by Morris Rosemberg created to explore the perception of self-esteem in people, this scale includes ten items that value feelings of respect and acceptance about oneself. Finally, the CD-RISC-10 scale designed by Connor and Davidson was used, which contains excellent psychometric properties and a high level of reliability, this scale has 25 items that allow to identify resilient behaviors, the aforementioned instruments were applied in the city of El Guabo to a 25-year-old with Friedreich's ataxia. The results obtained on the Rosemberg scale to measure his self-esteem yielded a score of 28, reflecting that the student maintains a medium level of self-esteem and in the application of the CD-RISC-10 Scale, in the sum of the 25 items a score of 70 is obtained, the same that frames a list of characteristics of high resilience. As a conclusion of our research work, we can highlight that the individual, thanks to resilience, has managed to build his existence after incorporating his own experiences, turning them into learning that produce "comfort".
En determinados momentos de la vida puede aparecer una discapacidad a consecuencia de un accidente o por efecto de una enfermedad degenerativa, como el caso de estudio que se aborda en la presente investigación, el cual se generó a partir de la Ataxia de Friedreich. Una discapacidad que sobreviene sin aviso, puede significar un desconcierto superior al recordar y comparar la vida anterior al acontecimiento o enfermedad. Es por ello que el presente trabajo tiene como objeto de estudio un estudiante universitario con Ataxia de Friedreich el mismo que conduce a plantear el siguiente problema científico: ¿Cómo influye la resiliencia y autoestima en un estudiante universitario que padece Ataxia de Friedreich?, para contestar esta interrogante hemos propuesto como objetivo general determinar la incidencia de la resiliencia y la autoestima en un estudiante con Ataxia de Friedreich. Con base a la teoría de soporte se ha decidido enfocar el presente trabajo desde un paradigma cualitativo/interpretativo, destacando los argumentos que del enfoque hermenéutico que se conjugan en el paradigma cualitativo para lograr la interpretación de la palabra emitida de forma verbal por el sujeto en estudio. Por consiguiente, para delimitar los niveles de resiliencia y autoestima se implementó una metodología cualitativa que otorga la facilidad de interpretar las situaciones que manifiesta el estudiante mediante la entrevista; de esta manera se pretende potencializar al objeto de estudio. Las herramientas que se utilizaron para la recolección de información fue la observación en primera instancia, luego la entrevista encargada de establecer un banco de preguntas estructuradas, así mismo la aplicación de la escala de Rosemberg diseñada por Morris Rosemberg creada para explorar la percepción de la autoestima en las personas esta escala incluye diez ítems que valoran sentimientos de respeto y aceptación sobre sí mismo. Por último, se empleó la escala de CD-RISC-10 diseñada por Connor y Davidson, la cual contiene excelentes propiedades psicométricas y un alto nivel de fiabilidad, esta escala cuenta con 25 ítems que permiten identificar conductas resilientes, los instrumentos mencionados fueron aplicados en la ciudad de El Guabo a un joven de 25 años con Ataxia de Friedreich. Los resultados obtenidos en la escala de Rosemberg para medir su autoestima arrojaron un puntaje de 28, reflejando que el estudiate mantiene un nivel de autoestima medio y en la aplicación de la Escala CD- RISC- 10, en la sumatoria de los 25 ítems se obtiene un puntaje de 70, el mismo que enmarca una lista de características de alta resiliencia. Como conclusión de nuestro trabajo de investigación podemos resaltar que el individuo gracias a la resiliencia ha logrado edificar su existencia después de incorporar sus propias vivencias, convirtiéndolas en aprendizajes que le produzcan “comodidad”.
Keywords: DISCAPACIDAD; RESILIENCIA; AUTOESTIMA; ADVERSIDAD; FAMILIA